2021
DOI: 10.1108/jsm-12-2020-0486
|View full text |Cite
|
Sign up to set email alerts
|

Signaling authenticity for frontline service employees

Abstract: Purpose Authenticity is a complex character that is valued in service contexts. Frontline service employees (FSEs), as both brand representatives and individuals who interact with clients, can signal their authenticity to customers. The purpose of this study is to investigate how FSEs signal their authenticity to customers. The authors investigate authenticity signal themes and develop a typology of how FSEs use these signals in the workplace. Design/methodology/approach This research uses a multi-method app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 62 publications
(111 reference statements)
0
1
0
Order By: Relevance
“…Research about the moral limits in services marketing is patchy, with a resurgence of interest in recent years. For example, Matthews and Eilert (2021) identified that displaying moral beliefs and behaviours signalled authenticity to service consumers; Okan and Elmadag (2020) explored the violation of moral codes in service environments; Söderlund (2021) highlighted morality as a fundamental human feature; Bove (2019) addressed moral recognition as a means to improve moral decision-making; and Cheung and McColl-Kennedy (2015) discussed moral economy logic and its place in transformative service logic.…”
Section: Introductionmentioning
confidence: 99%
“…Research about the moral limits in services marketing is patchy, with a resurgence of interest in recent years. For example, Matthews and Eilert (2021) identified that displaying moral beliefs and behaviours signalled authenticity to service consumers; Okan and Elmadag (2020) explored the violation of moral codes in service environments; Söderlund (2021) highlighted morality as a fundamental human feature; Bove (2019) addressed moral recognition as a means to improve moral decision-making; and Cheung and McColl-Kennedy (2015) discussed moral economy logic and its place in transformative service logic.…”
Section: Introductionmentioning
confidence: 99%